Optimalisasi Penggunaan Aplikasi Digital Dalam Teknik Penggambaran Struktur Bangunan - Andy Satria; Fajar Azhari Lubis; Zahroina Rosa Pasaribu (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The development of science and technology today is growing so rapidly, this has had a huge impact on human life. One example of technology that is developing so rapidly is the use of digital applications as a technique for depicting building structures. For example, these digital applications include AutoCAD, Revit and SketchUp design software. This application is a phenomenon that shows technological developments and the current needs of the architecture and construction industry. Depicting building structures using digital applications is the process of creating a digital model of the building to be built. a process of creating building engineering drawings in 3D (three-dimensional) form using computer applications that meet design standards. Digital applications can simplify and speed up the process of designing, implementing and maintaining buildings. Digital applications can also help save costs, time and resources, as well as reduce errors, conflicts and waste.